2017
DOI: 10.1016/j.pediatrneurol.2017.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Febrile Seizures and Epilepsy: Association With Autism and Other Neurodevelopmental Disorders in the Child and Adolescent Twin Study in Sweden

Abstract: In a nationally representative sample of twins, there was an increased rate of ESSENCE in childhood epilepsy and in febrile seizures. Febrile seizures alone could occur as a marker for a broader ESSENCE phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 29 publications
4
26
0
Order By: Relevance
“…In the Child and Adolescent Study in Sweden targeting twins born since July 1, 1992, parents of 27,092 twins were interviewed using a validated Diagnostic and Statistical Manual of Mental Disorders (DSM)-IV-based interview for early symptomatic syndromes eliciting neurodevelopmental clinical examinations (ESSENCE), in connection with the twins’ ninth or twelfth birthday. 106 ESSENCE refers to autism spectrum disorder, learning difficulty, developmental coordination disorder, and attention-deficit/hyperactivity disorder. The authors, however, found that the rate of ESSENCE in febrile seizures and epilepsy was significantly higher than in the total population without febrile seizures (all p <0.001).…”
Section: Complicationsmentioning
confidence: 99%
“…In the Child and Adolescent Study in Sweden targeting twins born since July 1, 1992, parents of 27,092 twins were interviewed using a validated Diagnostic and Statistical Manual of Mental Disorders (DSM)-IV-based interview for early symptomatic syndromes eliciting neurodevelopmental clinical examinations (ESSENCE), in connection with the twins’ ninth or twelfth birthday. 106 ESSENCE refers to autism spectrum disorder, learning difficulty, developmental coordination disorder, and attention-deficit/hyperactivity disorder. The authors, however, found that the rate of ESSENCE in febrile seizures and epilepsy was significantly higher than in the total population without febrile seizures (all p <0.001).…”
Section: Complicationsmentioning
confidence: 99%
“…Rather surprisingly, very few studies have investigated the possible co‐occurrence between FS and other neurodevelopmental, neuropsychiatric disorders, without referring to FS as a causative factor …”
Section: Introductionmentioning
confidence: 99%
“…Based on the aforementioned, altered expression of genes related to GABA and/or Glu might be linked to several ASD phenotypic features including cognitive deficits and/or hyperactivity (Jamain et al, 2002 ; Naaijen et al, 2017 ). Moreover, abnormalities in both neurotransmitters including an increase in the excitatory Glu and/or decrease in the inhibitory GABA were found to lead to epileptic seizure, a clinical feature which is commonly observed in ASD patients (Ballaban-Gil and Tuchman, 2000 ; Levisohn, 2007 ; Gillberg et al, 2017 ).…”
Section: Correlation Of Neurotransmitters Dysfunction To Asdmentioning
confidence: 99%